PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. TRI PUTRA MANDIRI - Lilis Muchlisa; Nuridin (Jurnal Ekonomi dan Industri, 2019)
This study aims to analyze the effect of work discipline and compensation on the performance of employees of PT. Tri Putra Mandiri. This study uses 2 independent variables, namely work discipline and compensation for employee performance. This research uses census method with 35 respondents. The analytical method used is multiple linear regression and simple. Based on the analysis of statistical data, the indicators in this study are valid and reliable. In testing classic assumptions, the regression model is problem-free multicollinearity, does not occur heteroscedasticity, and is normally distributed. The results showed that the work discipline variable had a positive and significant effect on employee performance, and the compensation variable had a positive and significant effect on employee performance. This research is expected to bring benefits to companies, and for academia and for future researchers to be developed by looking at other variables.